Supermassive star formation via super competitive accretion in slightly metal-enriched clouds. Issue 2 (4th April 2020) - Chon, Sunmyon; Omukai, Kazuyuki
ABSTRACT: Direct collapse black hole (DCBH) formation with mass ≳10 5  M⊙ is a promising scenario for the origin of high-redshift supermassive black holes. It has usually been supposed that the DCBH can only form in the primordial gas since the metal enrichment enhances the cooling ability and causes the fragmentation into smaller pieces. What actually happens in such an environment, however, has not been explored in detail. Here, we study the impact of the metal enrichment on the clouds, conducting hydrodynamical simulations to follow the cloud evolution in cases with different degree of the metal enrichment Z /Z⊙ = 10 −6 to 10 −3 . Below Z /Z⊙ = 10 −6, metallicity has no effect and supermassive stars form along with a small number of low-mass stars. With more metallicity $Z/\mathrm{ Z}_{\odot } \gtrsim5 \times 10^{-6}$, although the dust cooling indeed promotes fragmentation of the cloud core and produces about a few thousand low-mass stars, the accreting flow preferentially feeds the gas to the central massive stars, which grows supermassive as in the primordial case. We term this formation mode as the super competitive accretion, where only the central few stars grow supermassive while a large number of other stars are competing for the gas reservoir. Once the metallicity exceeds 10 −3  Z⊙ and metal-line cooling becomes operative, the central star cannot grow supermassive due to lowered accretion rate. Supermassive star formation by the super competitive accretion opens up a new window for seed BHs, which relaxes the condition on metallicity and enhances the seed BH abundance.